NEW APPROACHES IN NUTRITION: SOYMILK AND SOYMILK PRODUCTS - Oğuz GÜRSOY; Ramazan GÖKÇE; Özer KINIK (Pamukkale University Journal of Engineering Sciences, 1999)
Soybean, a protein rich product has an acceleration of increasing uses in different products. One of the usage of soybean is production and consumption as soymilk and soymilk products. These products, consumed in Far East for a long time, are introduced into the other countries in recent years and health conscious people are interested in them. These products, which have economic and as well as dietetic and therapeutic benefits, are not enough known in our country. In this review, general specifications, therapeutic and dietetic effects and production processes of soymilk, soy yogurt and soy cheese were discussed.